The Impact of Comprehending Islamic and Social Humanities Materials on Students' Perspectives on Resolving Contemporary Social Problems - Nur'aliya, Hanny Rizqiyana (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
This study aims to analyze the effect of understanding Islamic and Social Humanities material on student perceptions in addressing contemporary social issues in Indonesia. Using a mixed method approach, this study involved 100 2nd semester students of the Constitutional Law study program at UIN Sunan Kalijaga Yogyakarta who were selected through the random sampling method. Data were collected through attitude scales, questionnaires, interviews, and documentation, and analyzed using descriptive tests, normality tests, linear tests, and hypothesis testing with regression analysis. The results showed a positive relationship between understanding Islamic and social humanities courses and students' perceptions of contemporary social issues. The correlation is based on a significance value of 0.000 <0.05 and a coefficient of determination (R Square) of 0.585. So this study reveals that the understanding of Islamic and Social Humanities material explains 58% of the variability of student perceptions in addressing contemporary social issues. Students who have an open and critical attitude towards social issues show a good understanding of the course. The process of student understanding develops through several stages, ranging from initial knowledge to the development of complex new ideas. The role of lecturers in providing space for discussion, reflection, and open dialog is very important in facilitating a critical and holistic understanding of contemporary social issues in the context of Islam and the social humanities. Keywords: Islam and Social Humanities, Contemporary Social Issues, Understanding, Perception